Does hydroxychloroquine still have any role in the COVID-19 pandemic? - Schilling, WH; White, NJ (Taylor and Francis, 2021)
Introduction: The 4-aminoquinolines, chloroquine, and hydroxychloroquine have been used for over 70 years for malaria and rheumatological conditions, respectively. Their broad-spectrum antiviral activity, excellent safety profile, tolerability, low cost, and ready availability made them prime repurposing therapeutic candidates at the beginning of the COVID-19 pandemic.